THE IMPACT OF BRAND AUTHENTICITY AND BRAND COMMUNITY ON BRAND TRUST AND MSME GROWTH IN BUKALAPAK PARTNER APPLICATION USERS - Chelsy Philycia; Margaretha Pink Berlianto (Jurnal MEBIS (Manajemen dan Bisnis), 2022)
The massive growth of SMEs gave an opportunity to the tech industry in creating innovations. Applications with advanced and user-friendly features offered SMEs owners an opportunity to enlarge their businesses. This study’s objective is to discuss the impact of brand authenticity and brand community towards brand trust and SME growth in case of users of Mitra Bukalapak applications. This study uses bootstraping methods as the framework of theory analysis. In data collection, the study is using purposive sampling methtods to 362 community members of Mitra Bukalapak users. The result of this study found that brand consistency, brand customer orientation, brand community has a positive impact on brand trust, and brand trust has a positive impact on SME growth. Therefore, the study will contribute to current knowledge in the tech industry to build the brand and provide information on the impact of brand value development for the SME owners.